CLIENTELISM AND POLITICIZATION DIRECT INTERACTIONS BETWEEN DEPUTIES AND ‘ORDINARY CITIZENS’ IN FRANCE, CA. 1890-CA. 1940 - Beyen, Marnix (Temp - tidsskrift for historie, 2014)
ABSTRACT Clientelism and Politicization: Direct interactions between deputies and ‘ordinary citizens’ in France, ca. 1890-ca. 1940. This contribution contains a plea to consider the direct interactions between MPs and ‘ordinary citizens’ as an integral part of the complex phenomenon of political representation in modern democratic societies. During these interactions, the MPs and their respondents do not only defend each their personal interests, but often also articulate ideas about collective interests or even about the common good. As such, they are constitutive for the dynamic field of politics. By taking them into account, the Weberian thesis about a linear evolution from the ‘rule of notables’ to modern mass democracy should be reconsidered. The article proposes a multifaceted way of studying these interactive contacts, illustrating its method by focusing on a small group of left-wing MPs in France between 1890 and 1940. At a first stage, the letters received by the MPs are used in order to draw a social profile of the ‘ordinary citizens’ approaching their political deputies, to map their motives for doing so, and to trace the political knowledge and concepts articulated by them. In a second move, the interventions of the MPs in parliaments are scanned in search of explicit or implicit references to their contacts with these ordinary citizens. One general outcome of this preliminary research seems to be that these contacts follow a strikingly different pattern in rural than in urban or metropolitan constituencies. In the latter, the ‘ordinary citizens’ approached the MPs generally in a more or less direct way, whereas on the countryside these contacts were most often mediated by local administrations. As a result, these urban interactions tended much more than their rural counterparts to spur political dynamics.